2003
DOI: 10.1177/107834580300900402
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Co-payment on the Use of Medical Services by Male and Female Prisoners

Abstract: This study determined the effect of co-payment on the use of medical services by approximately 700 male and female prisoners in Idaho. Two way ANOVAs were computed to determine whether there were effects of gender, co-payment, and the interaction between gender and co-payment on the use of medical services. Findings included significant differences between male and female inmate medical requests after co-payment. Another finding was that the average number of requests significantly decreased for dental hygieni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…In one study, use of co-payments diminished the use of sick-call visits among male prisoners by 35%. 38 We are unaware of any recent studies that have assessed use of co-payments across state prison systems, but a 1996 survey found that co-payments were implemented or approved in 29 states, and introduction of legislation for prison co-payment was pending in an additional nine states. In states requiring a co-payment, fees ranged between two and five dollars.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, use of co-payments diminished the use of sick-call visits among male prisoners by 35%. 38 We are unaware of any recent studies that have assessed use of co-payments across state prison systems, but a 1996 survey found that co-payments were implemented or approved in 29 states, and introduction of legislation for prison co-payment was pending in an additional nine states. In states requiring a co-payment, fees ranged between two and five dollars.…”
Section: Discussionmentioning
confidence: 99%
“…There has not been a nationwide assessment of jail costs and causation, but a survey of governmental correspondence, budgets, and newspaper reporting reveals that local governments are reporting sharp increases in medical costs (Clouse, 2004;Dorgan, 2004;Garden, Shum, Buswell, Caverley, & Rees, 2003;Legislative Analyst's Office, 2001;Martin, 2004;Orleans Parish Criminal Sheriff 's Office, 2001). Strategies to reduce medical costs in local jails are a top priority for numerous jurisdictions and have included privatization, charging inmates co-pay fees, and purchasing inmate medical insurance (Allen & Pruett, 1996;Clark, 1994;Garden et al, 2003;Hyde & Brumfield, 2003;Szostak, 2002;Weiss, 1994).…”
Section: Cost Of Medical Care In Jailsmentioning
confidence: 99%
“…Another technique borrowed from the private sector (and from Medicare) is prisoner copayments. This has been shown by Hyde and Brumfield (2003) to be effective. They examine the initiation of small copayments ($3.00 for a sick care visit and $2.00 for a prescription) in Idaho prisons in 1998.…”
Section: Prison Healthcare Costs and Health Statusmentioning
confidence: 88%